2004
DOI: 10.1111/j.1460-9592.2004.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of premedication with OTFC, with or without ondansetron, on postoperative agitation, and nausea and vomiting in pediatric ambulatory patients*

Abstract: Even though OTFC reduced early postoperative agitation the increase in side effects, namely PONV and prolonged recovery times, limits its clinical usefulness. The study demonstrates the tradeoffs between anxiety and agitation vs vomiting, respiratory events and prolonged recovery times. Ambulatory pediatric patients undergoing procedures in which opioids would be routinely used might benefit the most from OTFC combined with ondansetron as part of the anesthetic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…2a. Twenty-one studies were excluded from the analysis because they reported zero events in all arms [39, 43, 57, 60, 61, 71, 73, 81, 82, 86, 90, 9294, 98, 110, 121, 127, 145, 155, 156]. Although the definitions of arrhythmia varied across the studies (Additional file 1: Appendix 10), there was no evidence of network inconsistency ( χ 2 = 3.49, degrees of freedom = 10, P = 0.968, heterogeneity variance = 0.01), and the within-network heterogeneity variance was estimated to be 0.00.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a. Twenty-one studies were excluded from the analysis because they reported zero events in all arms [39, 43, 57, 60, 61, 71, 73, 81, 82, 86, 90, 9294, 98, 110, 121, 127, 145, 155, 156]. Although the definitions of arrhythmia varied across the studies (Additional file 1: Appendix 10), there was no evidence of network inconsistency ( χ 2 = 3.49, degrees of freedom = 10, P = 0.968, heterogeneity variance = 0.01), and the within-network heterogeneity variance was estimated to be 0.00.…”
Section: Resultsmentioning
confidence: 99%
“…A subgroup analysis was conducted for 26 RCTs involving 4,878 patients in which the agents were administered during surgery [40, 43, 45, 53, 59, 74, 78, 79, 83, 86–89, 97, 102, 112, 113, 115, 117, 119, 123, 125, 132, 138, 142, 150]. The results were the same as for the primary analysis, except that significantly fewer patients of all ages receiving dolasetron experienced arrhythmia compared with placebo (OR 0.58, 95 % CI 0.36–0.93) and ramosetron (OR 0.38, 95 % CI 0.17–0.92) (Additional file 1: Appendix 13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined administration of ketamine and midazolam seems to be superior to that of midazolam alone [20,21], whereas rectal ketamine alone at a dose of 10 mg kg -1 seems at least as effective as rectal midazolam 1 mg kg -1 , but may lead to prolonged postoperative sedation with possible problems in cases of a brief surgery and with outpatients [8]. Oral fentanyl at a dose of 15 lg kg -1 has been reported to cause preoperative vomiting [22], although lower doses seem to be a safe alternative to midazolam [23], despite a higher rate of PONV; other authors [24] have recently confirmed that oral fentanyl can reduce early postoperative agitation but increases both PONV and recovery times, thus limiting its clinical usefulness. Rectal morphine, when compared to midazolam, shows similar postoperative and higher preoperative discomfort and is not advisable as an alternative to midazolam [25].…”
Section: Discussionmentioning
confidence: 97%
“…The aim of our study was to compare ketamine (10 mg kg -1 ), fentanyl (5 lg kg -1 ) plus droperidol (100 lg kg -1 ), and placebo, to assess which of them, if any, could be the best compromise among sedation, analgesia, and lack of perioperative side effects. The combination of fentanyl plus droperidol has been chosen in the attempt to achieve sedation and analgesia with lower PONV rather than higher doses of fentanyl alone [22][23][24]. Because of the lack of pharmacological data about rectal administration of fentanyl, we have assumed that the peak plasma level of both premedicants was attained about 45 min after rectal administration [8,33,34].…”
Section: Discussionmentioning
confidence: 99%